2011
DOI: 10.3928/01477447-20110228-02
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Rotator Interval Closure by Purse String Suture for Symptomatic Inferior Shoulder Instability

Abstract: Multidirectional instability of the shoulder is a complex condition that can be difficult to diagnose and treat. Clinically, it is characterized by symptomatic global laxity of the glenohumeral joint and may present either traumatically or atraumatically, unilaterally or bilaterally, and with or without generalized joint laxity. Capsular plication is a primary treatment option in these patients and is used to tension the redundant or lax capsule. We evaluated the role of rotator interval closure in restoring s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Finally, in case of failure the fact that only one anchor has been inserted makes revision simpler leaving space for revision anchors to be inserted [8]. The “purse- string” suture can also be used in the very complex group of patients with multidirectional instability after careful selection and knowledge of the technique can lead to successful results in this difficult to treat condition [16]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in case of failure the fact that only one anchor has been inserted makes revision simpler leaving space for revision anchors to be inserted [8]. The “purse- string” suture can also be used in the very complex group of patients with multidirectional instability after careful selection and knowledge of the technique can lead to successful results in this difficult to treat condition [16]. …”
Section: Resultsmentioning
confidence: 99%
“…This technique has been used to improve symptoms in multidirectional instability patients with more prominent antero- inferior instability symptoms. In 20 patients, at 2 years follow up, symptoms significantly improved and no re-dislocations were recorded [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Post surgical studies on athletes have reported both positive [66,67] as well as unsatisfactory [68] results on successful return to sporting activities at the top or pre-injury levels. The RI closure also leads to an improvement in both the static and the dynamic restraints which enhances the effect on the shoulder stability and function [69] . Despite the universal adoption of the arthroscopic practice, open procedures have shown good outcomes with an acceptable failure rate [70,71,72] .…”
Section: Resultsmentioning
confidence: 99%
“…This is a painful condition, which increases in severity if left untreated. Treatment options include surgical intervention, physiotherapy with specific strengthening exercises for muscle groups to better hold the shoulder in proper position, cortisone injections and anti-inflammatory medications (Bigliani et al 1996;Moon et al 2011). GAG (E) and Hydroxyproline (F) content of 3 to 12 week-old WT and Hspg2 ∆3-/∆3tail tendons.…”
Section: Ng2/cspg4 Is Another Transmembrane Proteoglycan Produced By mentioning
confidence: 99%